A novel reaction‐based fluorescent probe sensitive to pH changes in multiple intervals. (8th December 2020) - Li, Hongqi; Chen, Zhen; Zheng, Tao; Hu, Luping; Song, Yanxi; Zhang, Ruiqing; Zhang, Xin
Abstract: A new coumarin derivative containing both imine bond and amide moiety was synthesised. It was used as a reaction‐based pH probe and was sensitive to pH changes in the intervals 1.50–4.10 and 10.20–12.86. In the pH range 1.50–4.10, the ultraviolet‐visible (UV‒vis) absorption band of the probe gradually shifted from 353 nm to 340 nm with decrease in the pH value. The colour changed from pale yellow fluorescence at pH 4.10 to blue fluorescence at pH 1.50. Meanwhile the fluorescence emission band at 501 nm gradually shifted to 560 nm accompanying a gradual enhancing in the emission intensity. This pH response is caused by the hydrolysis of the imine bond in the probe under acidic conditions (pH 1.50–4.10). The colourless probe solution turned yellow at pH range 10.20–12.86. Bathochromic shift of the fluorescence band from 501 nm gradually to 550 nm was observed with the increase of pH value from 10.20 to 12.86 accompanying a gradual enhancement of the fluorescence emission intensity, indicating that the new compound serves as a fluorescent pH probe at pH range 10.20–12.86 through a deprotonation process. Under strongly alkaline conditions with pH larger than 12.86, hydrolysis of the lactone structure in the probe occurred to produce non‐fluorescent species.